Human Rights and Recent Trends: A Special Reference to Sri Lankan Genocide and India‟s Diplomatic Failure in the Indian Ocean Region - Geostrategic Politics - G. , Chandra Sekaran (International Journal of Psychosocial Rehabilitation, 2020)
This article explores the history of the Sri Lankan Tamil genocide and its international response. It also focuses on the China factor in the internal dynamics of Sri Lanka and how India lost its sphere of influence in Sri Lankan geopolitics and the Indian Ocean region. It has studied the implication of the civil war (Eelam War IV) in Sri Lanka and the final phase of the war, in which the Sri Lankan armed forces have violated human rights. It examines the present situation of Tamils in Sri Lanka, who are facing psychological warfare under the Sri Lankan government. This paper evaluates the failure of India’s diplomacy in the Indian Ocean region and the entry of China’s domination in the Indian Ocean region and its control of the sea lines of communications (SLOCs) by the help of the Sri Lankan government.